Measurement solubility of Acetylsalicylic Acid in water and alcohols - Ostadhashem, Amir Hosein; Peyvandi, Kiana (International Pharmacy Acta, 2021)
Low aqueous solubility of drug is one of the problems in pharmaceutical industry and the enhancement of the solubility of these poorly soluble drugs has recently attracted the consideration of researchers. In this way, one of the essential methods to overcome this challenge is to use co-solvents. In this study, a set of experiments was conducted to measure the solubility and density of Acetylsalicylic Acid as a painkiller drug in water, 1-octanol, ethanol, methanol, and ethylene glycol as solvents in the temperature range of 298 to 330 K. Furthermore, the experiments are carried out at 298K in the binary mixture of solvents to investigate the interaction effect of another solvent or anti-solvent in different percentages of mixtures. The results of this investigation revealed that using binary solution of water and ethanol, as a solvent aid, was able to increase the solubility especially in high percentage of ethanol. Moreover, to indicate the applicability of simple empirical model, the experimental data was used to optimize two adjustable parameters of the selected model. In future research, a successful thermodynamic models will be offered based on gathered data for prediction of solubility in the different temperature with high accuracy.